1998
DOI: 10.1097/00000658-199801000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of TGF-βs and Their Receptors in Human Acute Pancreatitis

Abstract: The marked increase in expression of TGF-betas and their signaling receptors Tbeta-RI (ALK5) and Tbeta-RII suggests a role for TGF-betas in the repair process after the onset of NP in humans and raises the possibility that TGF-betas might be involved in tissue remodeling and the fibrotic reaction that occurs in the pancreas after necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 39 publications
0
53
0
Order By: Relevance
“…In pulmonary arterial endothelial cells, BMP2 signaling has been shown to upregulate apelin expression (36), whereas BMP4, -7, and -9 were reported to downregulate apelin expression in pulmonary endothelial vascular cells (31). Our results showed that TGF-␤, a major signal behind the inflammation-fibrosis cascade in pancreatitis (10,23,39), upregulated PTHrP expression in acinar cells and PSCs. These findings were important since the present study showed that PTHrP upregulated pancreatic gremlin expression.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In pulmonary arterial endothelial cells, BMP2 signaling has been shown to upregulate apelin expression (36), whereas BMP4, -7, and -9 were reported to downregulate apelin expression in pulmonary endothelial vascular cells (31). Our results showed that TGF-␤, a major signal behind the inflammation-fibrosis cascade in pancreatitis (10,23,39), upregulated PTHrP expression in acinar cells and PSCs. These findings were important since the present study showed that PTHrP upregulated pancreatic gremlin expression.…”
Section: Discussionmentioning
confidence: 60%
“…BMP2 was shown to signal through Smad1 to reduce TGF-␤-stimulated fibrosis in PSCs (11). Additionally, BMPR2/Smad1/5/8 signaling exerted a protective role against Cer-induced fibrosis by inhibition of Smad2 and p38 (MAPK) pathways (10). Based on these activities and the discovery of a pancreatic BMP2-apelin-PTHrP network, we propose that the BMP2-apelin-PTHrP network functions to regulate the inflammation-fibrosis cascade of CP.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Of particular relevance to the latter point is the recent work by Friess et al (35,36) showing that increased expression of TGFh and VEGF in stromal areas of pancreatic cancer is associated with poor patient outcome.…”
Section: Discussionmentioning
confidence: 97%